2018
DOI: 10.1002/jmor.20817
|View full text |Cite
|
Sign up to set email alerts
|

Frontal sinus ontogeny and covariation with bone structures in a modern human population

Abstract: In humans, the frontal sinus (FS) is located in the medial part of the supraorbital region, sometimes expanded throughout the frontal squama. It exhibits high morphological variability, but its general form appears to be constrained by surrounding structures. The goal of this study is to analyze FS growth and test for covariation between FS volume and the glabellar region, upper nasal region, bone thickness and endocranial size in a human sample from Argentina. The sample comprises 149 reconstructions derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…Thus, this methodological study is able to assess effects of deviations on a broad range of individual sinus morphologies, as appropriate for our question. Although some studies have documented patterns in frontal sinus morphology between population, sex, or age groups or with variables such as body size and craniofacial morphology, these relationships are relatively weak [ 34 , 35 , 36 ], and the underlying factors contributing to such a high degree of frontal sinus variation, whether within or across groups, are unknown. These variations are described as differences in sinus appearance, size, and shape— all variables included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this methodological study is able to assess effects of deviations on a broad range of individual sinus morphologies, as appropriate for our question. Although some studies have documented patterns in frontal sinus morphology between population, sex, or age groups or with variables such as body size and craniofacial morphology, these relationships are relatively weak [ 34 , 35 , 36 ], and the underlying factors contributing to such a high degree of frontal sinus variation, whether within or across groups, are unknown. These variations are described as differences in sinus appearance, size, and shape— all variables included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…First, as with any ontogenetic variable, there is individual variation in the age at which final frontal sinus morphology is attained. In fact, studies already point to inherent noise in frontal sinus ontogenetic data (see Prossinger, 2004; Prossinger & Bookstein, 2003; Sardi et al, 2018). Radiographs were not available at every age for every individual in this study, and toward the older ages (20 yoa and above), sample sizes are greatly reduced—thus, there are some inherent gaps in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Sardi et al (2018) highlight a complicated ontogenetic relationship between frontal bone morphology and frontal sinus dimensions. Specifically, the cranial and sinus dimensions analyzed in their study showed drastically different ontogenetic trajectories across their sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations